Downstream process intensification for biotechnologically generated hyaluronic acid: Purification and characterization - Shukla P.; Srivastava P.; Mishra A. (My University, 2025)
Hyaluronic acid (HA), an anionic, non-sulfated glycosaminoglycan, has several clinical applications. This study examines several downstream methods for purifying HA with maximum recovery and purity. Following the fermentation of Streptococcus zooepidemicus MTCC 3523 to produce HA, the broth was thoroughly purified to separate cell debris and insoluble impurities using a filtration procedure and a variety of adsorbents for soluble impurities. Nucleic acids, proteins with high molecular weight, were successfully removed from the broth using activated carbons and XAD-7 resins. In contrast, insoluble and low molecular weight impurities were removed using diafiltration, with HA recovery of 79.16% and purity close to 90%. Different analytical and characterization procedures such as Fourier transform-infrared spectroscopy, X-ray diffraction, nuclear magnetic resonance, and scanning electron microscopy validated the presence, purity, and structure of HA. Microbial HA showed activity in tests for 2,2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH) radical-scavenging (4.87 ± 0.45 kmol TE/g), total antioxidant capacity (13.32 ± 0.52%), hydroxyl radical-scavenging (32.03 ± 0.12%), and reducing power (24.85 ± 0.45%). The outcomes showed that the precipitation, adsorption, and diafiltration processes are suitable for extracting HA from a fermented broth under the chosen operating conditions. The HA produced was of pharmaceutical grade for non-injectable applications. © 2023 The Society for Biotechnology, Japan